PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR PUSAT PERUM JASA TIRTA II KABUPATEN PURWAKARTA - Ca Meishyta Tritanti; H. Cecep Hermana (Ekonis: Jurnal Ekonomi dan Bisnis, 2022)
Abstract : In this study the authors used a quantitative research approach. The research population is the employees of the Central Office of Perum Jasa Tirta II Purwakarta Regency, totaling 280 employees. The sample of this study was 165 people. The sampling technique uses probability sampling, which is random sampling with the method used, namely systematic random sampling. The types of data are primary and secondary, the data sources are internal and external data. Collecting data through interviews, questionnaires and observation. Analysis of the data using a moderation test with the help of SPSS 24. Competence and work discipline have a simultaneous effect on employee performance by 0.742 or 74%. This shows that Competence and Work Discipline have a contribution to employee performance by 74% while the remaining 26% is a contribution from other variables not examined in this study. This shows that Competence and Work Discipline have a positive effect on employee performance. That is, the higher the competence and work discipline, the higher the employee performance.Keyword: Competence, Work Discipline, Employee Performance